Hankel determinant of order three for familiar subsets of analytic functions related with sine function - Arif, Muhammad; Raza, Mohsan; Tang, Huo; Hussain, Shehzad; Khan, Hassan (Open mathematics (Warsaw, Poland), 2019)
In this paper we define and consider some familiar subsets of analytic functions associated with sine functions in the region of unit disk on the complex plane. For these classes our aim is to find the Hankel determinant of order three.